Establishment of Penang prison under British in Malaya - Azlizan Mat Enh,; Siti Alwaliyah Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article discusses the institution of prison under the British administration in the Penang Prison in the 19th and the 20th century. Penang as an important port in the northern Malaya under the British administration has led to an increase number of people in the state who are immigrants besides the natives. Sudden boast in the population had led to an increase in criminal activities on the island that had disrupted the British administration. Penang which used the local customary law of Kedah Government had failed to control the criminal activities in Penang. Thus British introduced Western law in Penang to control the criminal activities on the island. The objective of this article is to analyze the factors for the establishment of the Penang Prison and its enforced regulations in the prison system of Penang to prisoners and prison officers. The methodology used to achieve this objective is through research on primary sources obtained from the national archive such as the Straits Settlements Departmental Annual Report, Rules And Regulations Under Ordinance No. XIV of 1872, Federated Secretariat 14250 / 49.1949, letters and files related to the prison rules. The study found that the enforcement of British system on the rules and regulations of Penang Prison has an important contribution because it has introduced a systematic prison system.